Ectopic germinal centers in the nasal turbinates contribute to B cell immunity to intranasal viral infection and vaccination - Romain Gailleton; Nimitha R. Mathew; Laura Reusch; Karin Schön; Lydia Scharf; Anneli Strömberg; Andrea Cvjetkovic; Luaay Aziz; Johan Hellgren; Ka-Wei Tang; Mats Bemark; Davide Angeletti (Proceedings of the National Academy of Sciences, 2025)
The nasal mucosa is the first immunologically active site that respiratory viruses encounter and establishing immunity at the initial point of pathogen contact is essential for preventing viral spread. Influenza A virus (IAV) in humans preferentially replicates in the upper respiratory tract (URT) but mouse models of infection result in lower respiratory tract infection. Here, we optimize IAV inoculation to enhance replication in the nasal turbinate (NT) and study local B cell immunity. We demonstrate that URT-targeted IAV infection stimulates robust local B cell responses, including germinal center (GC) B cell formation in the NT, outside of classical nasal-associated lymphoid tissues. NT GC contributes to local tissue-resident B cell generation and enhances local antibody production. Furthermore, URT-focused immunization also induces significant GC formation in the NT. Finally, we detect steady-state GC in the NT of both mice and healthy humans, suggesting continuous immune surveillance triggered by environmental stimuli. These findings highlight the pivotal role of the NT in local and systemic immunity, with important implications for future mucosal vaccines targeting the upper airways.